Thursday
March 23, 2017

Post a New Question

Posted by on Wednesday, May 14, 2008 at 9:55pm.

3(4^x)-2^(x+2) = -1

  • pre-calculus - , Wednesday, May 14, 2008 at 11:51pm

    3(4^x)-2^(x+2) = -1

    3(2^2)^x - (2^x)(2^2) + 1 = 0
    3(2^x)^2 - 4(2^x) + 1 = 0
    let 2^x = m

    3n^2 - 4m + 1 = 0
    (3m - 1)(m - 1) = 0
    m = 1/3 or m = 1

    so 2^x = 1/3
    x = ln(1/3)/ln2 = appr. -1.585

    or

    2^x = 1
    x = 0

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question